Resveratrol, Wine, and Atherosclerosis - Prasad, Kailash (International Journal of Angiology, 2012)
This review emphasizes the effects of resveratrol on factors involved in the mechanism of atherosclerosis and risk factors for atherosclerosis. The effects of wine and resveratrol on atherosclerosis are also discussed. Resveratrol is a potent antioxidant and an anti-inflammatory agent. It reduces the expression of cell adhesion molecules, monocyte colony stimulating factors, matrix metalloproteinases, and growth factors; and inhibits platelet aggregation and vascular smooth muscle cell proliferation. It reduces the serum levels of total cholesterol, triglycerides (TG), and raises high-density lipoprotein cholesterol, inhibits expression of C-reactive protein and lowers the levels of advanced glycation end products and its receptor in the vascular tissue. It lowers the risk factors for plaque rupture. Epidemiological data show that moderate consumption of alcohol has an inverse association with carotid atherosclerosis while high consumption has a positive association with carotid atherosclerosis. Wine reduces the extent of atherosclerosis in animal model. The antiatherosclerotic effect of wine is mainly due to it resveratrol content. Resveratrol reduces the extent of atherosclerosis in animal model of atherosclerosis (apolipoprotein [Apo] E-deficient and Apo E−/−/low-density lipoprotein receptor-deficient mice and macrophage). In rabbit model of atherosclerosis, both reduction and acceleration of atherosclerosis have been reported with resveratrol. There are no data for regression and slowing of progression of atherosclerosis. Robust clinical trials for suppression of atherosclerosis are lacking. In conclusion, resveratrol has potential but experimental studies in depth and robust clinical trials are lacking for this agent to be of any value in the primary and secondary prevention of coronary and peripheral artery disease.
Keywords: resveratrol; atherosclerosis; serum lipids; inflammatory mediators; C-reactive protein; wine; growth factors; vascular smooth muscle cell proliferation; matrix metalloproteinase